2019 19th International Symposium on Communications and Information Technologies (ISCIT) 2019
DOI: 10.1109/iscit.2019.8905159
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Cooperative Repair Scheme for Reed-Solomon Codes

Abstract: Dau et al. recently extend Guruswami and Wootters' scheme (STOC'2016) to cooperatively repair two or three erasures in Reed-Solomon (RS) codes. However, their scheme restricts to either the case that the characteristic of F divides the extension degree [F : B] or some special failure patterns, where F is the base field of the RS code and B is the subfield of the repair symbols. In this paper, we derive an improved cooperative repair scheme that removes all these restrictions. That is, our scheme applies to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Both perform the same steps during the Download Phase but follow different procedures in the Collaboration Phase: the one-round procedure allows the two RNs to exchange all − m missing traces at once while the multi-round allows the missing traces to be recovered batch-by-batch. Note that in [6], [17], [20], only one missing trace needs to be recovered in the Collaboration Phase, which is easier to handle.…”
Section: Repairing Two Erasures In Reed-solomon Codesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both perform the same steps during the Download Phase but follow different procedures in the Collaboration Phase: the one-round procedure allows the two RNs to exchange all − m missing traces at once while the multi-round allows the missing traces to be recovered batch-by-batch. Note that in [6], [17], [20], only one missing trace needs to be recovered in the Collaboration Phase, which is easier to handle.…”
Section: Repairing Two Erasures In Reed-solomon Codesmentioning
confidence: 99%
“…There has been a considerable effort by the research community to improve and optimize the repair bandwidth of Reed-Solomon codes [9]- [16]. Several extensions to the case of multiple erasures were also studied [6], [16]- [20]. The optimal repair bandwidth of Reed-Solomon codes is generally unknown, except for some full-length codes [1], [10], [11] and for codes with exponentially large subpacketizations [15], [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the repair schemes for two failed symbols in [26] are either confined to the case of char(F ) | t, or demand a sequential repair of the two erasures, where char(F ) represents the character of the finite field F . An improved distributed repair scheme with two erasures of RS codes was proposed in [27], which eliminates all limitations of [26]. When n − k ≥ |B| m , 1 ≤ m < t, [28] displayed some distributed repair schemes with one or more rounds, which can repair two failed symbols of RS codes by applying subspace polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…More surprisingly, in recent years a new interest in these codes has risen in the research community. It is caused by the fact that they are extensively used in cloud technology, namely in distributed storage systems [5,6,7,8,9]. In [1] it was shown that RS codes could be extended not only three times, but even five times when they are constructed over certain finite fields.…”
Section: Introductionmentioning
confidence: 99%